(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
The aim of the study is to identify the most frequent markers in two formal television interviews and subsequently to consider the discursive values and realisation level of these markers within the discourse. It thus involves a closer look at television language, which is representative of a certain social level in Chile. In addition, the study offers other perspectives on grammar teaching that focus on extensive discourses and shows that the grammatical function of the discursive markers exists not only at an interdiscursive level, but also at a macrodiscursive level, taking into consideration the different parts of a discourse.